Nearly Primary-2-Absorbing Submodules and other Related Concepts - Ali Sh. Ajeel; Omar A. Abdulla; Haibat K. Mohammadali (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2021)
Our aim in this paper is to introduce the notation of nearly primary-2-absorbing submodule as generalization of 2-absorbing submodule where a proper submodule  of an -module  is called nearly primary-2-absorbing submodule if whenever , for , , ,  implies that either  or  or . We got many basic, properties, examples and characterizations of this concept. Furthermore, characterizations of nearly primary-2-absorbing submodules in some classes of modules were inserted. Moreover, the behavior of nearly primary-2-absorbing submodule under -epimorphism was studied.